Notary's Responsibility for the Material Truth of Capital Deposit by the Founder in the Deed of Establishment of Limited Liability Company - Rachmadhani, Salsabila Sekar; Sudarwanto, Albertus Sentot; Najicha, Fatma Ulfatun (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
This research discusses the responsibility of notaries in relation to the material truth of the deposit of capital by the founders in the deed of establishment of a Limited Liability Company. The purpose of this research is to analyze the extent of notary’s responsibility when there is negligence in depositing capital by the founder and the deed of establishment is declared to be null and void. This research is a normative legal research with a legislative and case approach. The results of the study show that the notary is only responsible for the formal correctness of the deed made. The court decision that annuls the deed of establishment due to the negligence of the founders is considered inaccurate, because it blurs the boundary of responsibility between the founder and the notary, and can undermines the principle of legal certainty.